Genome‐wide association study reveals significant loci and candidate genes for fruit branch length in upland cotton - Hui Chang; Honghu Ji; Ruijie Liu; Juling Feng; Jiayi Wang; Shuqi Zhao; Wei Li; Zehua Qiu; Nabil Ibrahim Elsheery; Shuxun Yu; Libei Li; Zhen Feng (The Plant Genome)
Abstract The length of fruit branches significantly influences plant architecture in upland cotton (Gossypium hirsutum L.), which is crucial for optimizing fiber yield and quality. In this study, a comprehensive genome‐wide association study was conducted based on whole‐genome resequencing data that identified 249 significant SNPs associated with fruit branch length (FBL), forming 79 distinct quantitative trait loci (QTL) regions. Notably, stable QTL regions qFBL‐A10‐4 and qFBL‐D03‐17 were identified, harboring key candidate genes such as Ghir_A10G014390 and Ghir_D03G011390. Superior haplotypes of these genes significantly enhance FBL, fiber yield, and quality, offering valuable targets for cotton breeding programs focused on optimizing plant architecture and productivity.